THE INFLUENCE OF LEARNING STRATEGY AND LEARNING MOTIVATION ON THE RESULTS OF ISLAMIC EDUCATION IN SMPN 45 MEDAN - Siti Fatimah (Universitas Islam Negeri Sumatera Utara Medan, 2019)
The purpose of this study was to find out and describe: (1) the effect of theapplication of learning strategies on the learning outcomes of students'Islamic Education, (2) the effect of learning motivation on student IslamicEducation learning outcomes, and (3) the interaction between learningstrategies and learning motivation towards learning outcomes of students'Islamic Education.The method of this research is quasi-experimental withthe population of this study are VII grade students of SMPN 45 Medanconsisting of 5 classes. The sample was selected by cluster randomsampling technique in this case taken one simulation learning strategy andone class taught with expository strategies. The instruments of datacollection are questionnaires and test results. Technique by analysis ofvariance (Anava) at = 0.05. The results of this study are: (1) the averagestudent learning outcomes taught with simulation learning strategies higher than the average student learning outcomes learned by theexpository learning strategy, (2) the average learning outcomes ofstudents with high learning motivation higher than the learning outcomesof students with low learning motivation, and (3) there is an interactionbetween learning strategies and learning motivation towards learningoutcomes.